STANDARDISATION AND PRICING OF MAIZE COMMODITIES FROM THE MABI' PERSPECTIVE IN SALE AND PURCHASE CONTRACTS - Mutia Sahara Ningsih (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2021)
The market mechanism plays a very important role in changing the price of a commodity. One of them is in the price mechanism for shelled corn in the Deleng Pokhkisen District area, farmers sell their corn harvest to collectors. This is a dilemma for the farmers, because the collectors have set a standardized price for corn that is slightly lower than the factories. Therefore, writing this thesis examines how the mechanism for standardization and pricing of shelled corn occurs in Deleng Pokhkisen District from a mabi' perspective. This research was carried out using a qualitative approach, with a normative-empirical type of research. The results showed that the corn price setting mechanism followed the price changes given by the factory. The collectors who buy the farmer's corn will sell it back to the factory with a profit difference of Rp. 200/kg to Rp. 500/kg. In addition, changes in the rise and fall of corn prices are not carried out unilaterally by the collectors or the factory. Fluctuations in the price of shelled corn are influenced by the actual market price demand mechanism, such as the influence of consumer demand for animal feed. In the perspective of Islamic law, transactions carried out by farmers, agents and manufacturers are in accordance with the provisions of Islamic law in the principles of transactions that require the willingness of each party, without being based on price manipulation and bad intentions.